Steady-state free precession for T2 relaxometry: all echoes in every readout with k-space aliasing - Lally,P; Jin,Y; Huo,Z; Beitone,C; Chiew,M; Matthews,P; Miller,K; Bangerter,N (Magnetic Resonance in Medicine, 2025)
PurposeMulti-echo gradient echo imaging is useful for a range of applications including relaxometry, susceptibility mapping, and quantifying relative proportions of fat and water. This relies primarily on long-TR multi-echo gradient echo sequences (FLASH), which by design isolate one signal component (i.e., echo) at a time per readout. In this work, we propose an alternative strategy that simultaneously measures all signal components at once in every readout event with an N-periodic SSFP sequence. Essentially, we Fourier encode the signals into an “F-k space” similar to the “TE-k space” of a multi-echo gradient echo acquisition. This enables an efficient, short-TR relaxometry experiment where signals benefit from averaging effects over multiple excitations.Theory and MethodsIn the presented approach, multiple echoes are recorded simultaneously and separated by their differing phase evolution over multiple TRs. At low flip angles the relative echo amplitudes and phases are equivalent to those acquired sequentially from a multi-echo FLASH, in terms of both T2 weighting and spatial phase distributions. The two approaches were compared for the example of R2 relaxometry in a phantom and in human volunteers.ResultsThe proposed approach shows close agreement in R2 estimation with multi-echo FLASH, with the advantage of more rapid temporal sampling.ConclusionThe proposed approach is a promising alternative to other relaxometry approaches, by measuring signals from multiple echo pathways simultaneously and separating them based on a simple analytical model.